A powerful molecular marker to detect mutations at sorghum LOW GERMINATION STIMULANT 1 - Adedayo O. Adeyanju; Patrick J. Rich; Gebisa Ejeta (The Plant Genome)
Abstract The parasitic weed Striga (Striga hermonthica) limits productivity of sorghum (Sorghum bicolor) and other cereals in sub‐Saharan Africa and elsewhere. Improved host plant genetics is an effective control method but verified loci contributing to Striga resistance are limited. LOW GERMINATION STIMULANT 1 remains the only known sorghum locus affecting resistance to Striga. Functional loss (lgs1) alleles at this locus result in low Striga germination stimulant activity. We developed a robust polymerase chain reaction (PCR)‐based LGS1 marker that detects all known natural lgs1 alleles. We have successfully used this marker to improve Striga resistance in our sorghum breeding program. To check its utility among diverse sets of germplasm, we genotyped 406 lines of the sorghum association panel (SAP) with the marker and phenotyped them for Striga germination stimulant activity. The SAP contains 23 lines (6%) with lgs1 mutations that involve a complete loss of this gene. Three previously described deletion alleles (lgs1‐1, lgs1‐2, and lgs1‐3) ranging from 28.5 to 34 kbp are present among SAP members with a new one, lgs1‐6, missing nearly 50 kbp relative to the reference genome. All 23 members of the SAP carrying lgs1 alleles had low Striga germination stimulant activity. The smaller previously described intragenic deletion mutations lgs1‐4 and lgs1‐5 are not present in the SAP. The LGS1 marker is useful for both detecting sources of lgs1 and introgressing Striga resistance into new genetic backgrounds.